Education on acne and cosmetic knowledge for adolescents at SMK Rise Kedawung - Nur Rahmi Hidayati; Sulistiorini Indriaty; Arsyad Bachtiar; Choirun Annisah; Alya Suciyanti; Hilma Aynun Rahmatillah (Universitas Muhammadiyah Magelang, 2024)
Acne occurs due to the presence of S. Aureus bacteria, when the oil glands in the skin are too active, acne usually appears on the surface of the skin of the face, neck, chest, and back. Therefore, antibacterials are needed to overcome this, which can be obtained from chemicals or traditional plants. The aim of this community service program is to provide education to students at Rise Kedawung Vocational School about acne on teenage skin and training to check cosmetics registration using the BPOM Mobile application. This activity is carried out by providing material about acne starting from understanding acne, the causes of acne, traditional plants that have antibacterial activity, chemicals that have antibacterial activity, and how to check BPOM registration. The pre-test and post-test results showed an increase in participants' understanding regarding acne, acne medication, and checking cosmetic registration from 87% to 96%.